1975
DOI: 10.4315/0022-2747-38.7.388
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent light-Activated Flavor in Milk1

Abstract: Homogenized milk packaged in polyethylene containers exposed to fluorescent lights showed flavor and vitamin deterioration. Off-flavor development began within 2 to 4 h after exposure to a lighting system simulating commercial display cases. Detection of light-induced flavor was slight, medium, and strong after 4, 7 and 24 h of exposure. Decreases in riboflavin and ascorbic acid were directly proportional to the amount of light exposure. Various types of colored lamps and lamp filters were tested to prevent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…Likewise, Erickson (1997) reported a significantly higher degree of lipid oxidation for samples packaged in HDPE jugs as compared to samples packaged in paperboard cartons after 8 days of storage. The author attributed such differences to the light transmission properties of the packaging material (Hansen, Turner, & Aurand, 1975).…”
Section: Resultsmentioning
confidence: 98%
“…Likewise, Erickson (1997) reported a significantly higher degree of lipid oxidation for samples packaged in HDPE jugs as compared to samples packaged in paperboard cartons after 8 days of storage. The author attributed such differences to the light transmission properties of the packaging material (Hansen, Turner, & Aurand, 1975).…”
Section: Resultsmentioning
confidence: 98%
“…Mortensen, Sørensen, Danielsen, et al (2003) and reported odor changes in sliced Havarti cheese already after 4 to 6 h of exposure to soft white fluorescent light, as well as to the specific wavelengths 405 and 436 nm. Significant flavor changes in milk after exposure to fluorescent light were observed after 2-6 h (deMan, 1978;Hansen et al, 1975;Whited, Hammond, Chapman, & Boor, 2002). Fig.…”
Section: Sensory Analysismentioning
confidence: 88%
“…Even more specific were Mortensen, Sørensen, Danielsen, and Stapelfeldt (2003), who analyzed the effect of light exposure to Havarti cheese for the single wavelengths 366, 405, and 436 nm. Also, milk has been exposed to light of different colors by using sleeves and light sources with well-defined spectral properties (Hansen, Turner, & Aurand, 1975). It was found that white fluorescent light was most harmful, inducing formation of off-favors after a few hours.…”
Section: Introductionmentioning
confidence: 99%
“…The light-activated oxidation products result in very pronounced off-flavors, which have an adverse effect on consumer acceptance (Patton, 1953;Allen & Parks, 1975;Hansen, Turner, & Aurand, 1975;Dimick & Kilara, 1983;Kim & Morr, 1996). The light-induced off-flavors that become noticeable relatively early are derived from protein oxidation while later in the oxidation progress off-flavors derived from lipids become dominating (Dunckley, Frankel, & Pangborn, 1962;Dimick & Kilara, 1983;Marsili, 1999).…”
Section: Introductionmentioning
confidence: 95%